Transnational feminist solidarity in times of crisis - Sharoni, Simona; Siddiqi, Dina Mahnaz; Abdulhadi, Rabab; Al-Ali, Nadje; Eaves, Felicia; Lentin, Ronit; Eaves, Felicia (© 2015 Taylor & Francis, 2016)
This review was published in International Feminist Journal of Politics [© 2015 Taylor & Francis] and the definite version is available at: https://www.google.com/search?q=10.1080%2F14616742.2015.1088226&ie=utf-8&oe=utf-8&client=firefox-b The article website is at: http://www.tandfonline.com/doi/abs/10.1080/14616742.2015.1088226?needAccess=true